Maslow's and Freud's Theories Reflected in Andrew Laeddis' Character - Novelia Hutagaol, Friskila Yesika; Widyaningrum, Agnes (LPPM Universitas Bumigora Mataram, 2023)
This research explores the portrayal of schizophrenia symptoms in the character Andrew Laeddis from the movie